A New Total Order for Triangular Fuzzy Numbers with an Application - Valentina Rosas; Benjamín Bedregal; José Canumán; Roberto Díaz; Mansilla Villarroel, Jose Edmundo; Zumelzu Carcamo, Nicolas Eduardo (My University, 2021)
This work deals with the study of a new total order Triangular Fuzzy Numbers and arithmetic properties that are maintained in relation to the operations of addition and subtraction. Additionally, we present as example of application the shortest path solution for the Travelling Salesman Problem with fuzzy distances.
Keywords: Subtraction